2015
DOI: 10.1097/hp.0000000000000300
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Quantification of Delayed Radiation-Induced Organ Damage in Highly Irradiated Rats With Bone Marrow Protection

Abstract: The evolution of organ damage following extensive high-dose irradiation remains largely unexplored and needs further investigation. Wistar rats [with or without partial bone marrow protection (∼20%)] were irradiated at lethal gamma-ray doses (12, 14, and 16 Gy) and received antibiotic support. While total-body-irradiated rats did not survive, bone marrow protection (achieved by protecting hind limbs behind a lead wall) combined with antibiotic support allowed survival of 12-Gy and 14-Gy irradiated rats for mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…Similar to our studies, Booth et al also observed long-term damage to the murine intestine, including microadenomas, thicker submucosa, shorter crypts and villi, and increased collagen, extending 125 to 200 days post-PBI with 40% bone marrow shielding (9). In Wistar rats that received 12 Gy and 14 Gy irradiation with approximately 20% bone marrow sparing also showed decreased villus height even after 64 and 104 days postirradiation (36). In total, these findings indicate that PBI can exert long-lasting mucosal damage in animals irrespective of species.…”
Section: Discussionsupporting
confidence: 90%
“…Similar to our studies, Booth et al also observed long-term damage to the murine intestine, including microadenomas, thicker submucosa, shorter crypts and villi, and increased collagen, extending 125 to 200 days post-PBI with 40% bone marrow shielding (9). In Wistar rats that received 12 Gy and 14 Gy irradiation with approximately 20% bone marrow sparing also showed decreased villus height even after 64 and 104 days postirradiation (36). In total, these findings indicate that PBI can exert long-lasting mucosal damage in animals irrespective of species.…”
Section: Discussionsupporting
confidence: 90%
“…However, the primate studies were done without bone marrow sparing and therefore involved much lower doses of irradiation (<10 Gy). A study with male Wistar rats irradiated with 12 or 14 Gy PBI with both hind legs shielded (Boittin et al 2015), supports the role of antibiotics for enhancing survival. That group detected bacterial infection in blood cultured pre-mortem following 14 Gy, in which rats not given Enrofloxacin died by 10 days, probably due to bacterial translocation from GI injury.…”
Section: Discussionmentioning
confidence: 84%
“…The ability of surviving BM hematopoietic progenitor cells (HPC), either localized to a marrow site or dispersed throughout the total marrow space, to accelerate hematopoietic recovery after highly myelosuppressive irradiation has been consistent and is model independent, be it partial-body with marrow shielding/sparing, or unilateral, non-uniform total-body exposure in several animal species (Maillie et al 1966;Cole et al 1967;Wise and Turbyfill 1968;Gidali and Lajtha 1972;Maloney and Patt 1972;Monroy et al 1988;Wang et al 1991;Geraci et al 1992;Bertho et al 2005a;Booth et al 2012;Herodin et al 2012;MacVittie et al 2012a;Drouet et al 2014;Boittin et al 2015). The critical condition is the differential dose distribution throughout the tissue and the basic assumptions that hematopoietic recovery from the H-ARS is dependent on the survival of a critical fraction of HPC that are equally distributed throughout the active marrow tissue, independent of location and equivalent in regenerative ability (Bond and Robinson 1967;Taketa et al 1970;Bond et al 1991;Campbell et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These conditions forecast the sparing of variable amounts of critical organ tissue that will define the severity of the ARS and DEARE. The sparing of BM, GI, lung, heart and/or kidney tissue, can have dramatic effects on the incidence, latency, severity, progression and resolution of organ-specific and organ-interactive sequelae (Ainsworth et al 1965;Cole et al 1967;Wise and Turbyfill 1968;Rauchwerger 1972;Monroy et al 1988;Mason et al 1989;Terry and Travis 1989;Geraci et al 1990;Guskova et al 1990;Geraci et al 1992;Liao et al 1995;Bertho et al 2005a;Novakova-Jiresova et al 2005;van Luijk et al 2007;Drouet et al 2008;Granton et al 2014;Boittin et al 2015). Non-uniform and/or heterogeneous exposure with or without medical management will change the organ-specific dose response relationships (DRR) for morbidity and mortality throughout the ARS and DEARE (Ainsworth et al 1965;Wise and Turbyfill 1968;Evans et al 1987;Baranov and Guskova 1990;Guskova et al 1990;Herodin et al 2007;MacVittie et al 2012a).…”
Section: Discussionmentioning
confidence: 99%